2011
DOI: 10.1007/s10549-011-1672-2
|View full text |Cite
|
Sign up to set email alerts
|

Distinct expressions of microRNAs that directly target estrogen receptor α in human breast cancer

Abstract: Estrogen receptor (ER) α is essential for estrogen-dependent growth, and its level of expression is a crucial determinant of response to endocrine therapy and prognosis in ERα-positive breast cancer. Breast cancer patients show a wide range of ERα expression levels and the levels of expression in individual patients change during disease progression and in response to systemic therapies. However, little is known about how the expression of ERα in human breast cancer is regulated. Recently, several microRNAs (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 36 publications
5
57
3
Order By: Relevance
“…The differential expression observed in our study demonstrates that TN breast carcinomas are characterized by the expression of miRNAs that downregulate ESR1 expression, such as let-7b (Zhao et al 2011a,b, Quesne et al 2012) and miR-18a/b (Leivonen et al 2009, Liu et al 2009, Yoshimoto et al 2011. According to this observation, we found that miR-934 was the most significantly modulated miRNA in TN breast cancer, and confirmed this by our analyses of data from the TCGA database (2012).…”
Section: Discussionsupporting
confidence: 85%
“…The differential expression observed in our study demonstrates that TN breast carcinomas are characterized by the expression of miRNAs that downregulate ESR1 expression, such as let-7b (Zhao et al 2011a,b, Quesne et al 2012) and miR-18a/b (Leivonen et al 2009, Liu et al 2009, Yoshimoto et al 2011. According to this observation, we found that miR-934 was the most significantly modulated miRNA in TN breast cancer, and confirmed this by our analyses of data from the TCGA database (2012).…”
Section: Discussionsupporting
confidence: 85%
“…It has been reported that miR-18b has a role as a tumor suppressor gene by targeting the MDM2-p53 pathway in melanoma (11). Moreover, miR-18b is abnormally expressed in gastric cancer (12), breast cancer (13) and nasopharynx cancer (14). The present study indicated that miR-18b exhibited pathologically low expression levels in PE placentas; however, the pathological mechanism of miR-18b in the pathogenesis of PE remains poorly studied (15).…”
Section: Introductionmentioning
confidence: 49%
“…We recently analyzed expressions of microRNAs (miRNAs) that directly target ER in breast cancer. We found that miR-206 and miR-18a were downregulated in ER-positive breast cancer compared with ER-negative tumors and that low miR-18b expression was significantly associated with improved survival in HER2-negative breast cancer, although miR-18b expression was not correlated with ER protein expression (Kondo et al 2008, Yoshimoto et al 2011.…”
Section: Introductionmentioning
confidence: 87%
“…Among differentially expressed 67 miRNAs, the above 12 miRNAs, especially let-7a, miR-10a, miR-10b, miR-15a, miR-26a, miR-29c, miR-34a, miR-146a, and miR-342-3p, have been reported to be related to breast cancer development and carcinogenesis (Mattie et al 2006, Blenkiron et al 2007, O'Day & Lal 2010. miR-193b has been reported to be related to ERa (Yoshimoto et al 2011). Moreover, we referred to the reported mRNA microarray analyses to classify luminal A and luminal B subtypes in order to select key genes (Sorlie et al 2003, Parker et al 2009), including FOXA1, NAT1, MAPT, XBP1, and BCL2, which have target sequences in the 3 0 -UTR regions of 67 differentially expressed miRNAs according to in silico analysis using TargetScan, PicTar, and MiRanda, and selected miR-146a and miR-1290, which were downregulated in ER high Ki67 low tumors.…”
Section: Western Blottingmentioning
confidence: 99%